Discongruence Index: predictor of prosthesis size loss after transcatheter aortic valve replacement. (14th October 2021) - De Agustin Loeches, J.A; Pozo, E; Nombela- Franco, L; Jimenez-Quevedo, P; Tirado, G; Mahia, P; Marcos-Alberca, P; Luaces, M; Perez De Isla, L; Gomez De Diego, J.J; Cobos, M.A; Islas, F; et al.
Abstract: Introduction: Prosthesis under-expansion has been associated with higher rates of complications and worse long term outcome after transcatheter aortic valve replacement (TAVR). The objective of the current study was to assess the value of a new "Discongruence index", to predict the percentage of prosthesis size loss (compared to its nominal size). The "discongruence index" is obtained from the relation between transcatheter valve size and the patient body surface area. Methods: A total of 247 consecutive patients with severe aortic stenosis that underwent TAVR with balloon expandable Edwards-Sapiens prosthesis or CoreValve Revalving system at our institution were included. The "Discongruence index" was calculated pre-procedurally as the ratio: selected transcatheter valve size (mm) / body surface area (cm 2 ). Two-dimensional transesophageal echocardiography images were studied in the 120–135° plane after the prosthesis deployment, and the maximum anteroposterior diameter was measured (in millimeters). From this measurement was obtained the percentage of prosthesis size loss (compared to the prosthesis nominal size). Results: Mean age was 82±6 years and 102 patients (41.3%) were men. Mean aortic valvular area before TAVR was 0, 87±3, 8 cm 2, (indexed 0, 36±0, 1 cm 2 ) and the mean aortic gradient 49, 1±16, 9 mmHg. Mean prosthesis maximum deployment was 18, 9±2, 7 mm; absolute loss of prosthesis size compared to nominal 6, 5±2, 8 mm and the percentage loss of prosthesis size 25.1±9, 5%. The "Discongruence index" was predictor of the percentage of prosthesis size loss (y = 5, 7650 + 1, 3010x, p<0, 001), see figure. Conclusions: The "Discongruence index" is a useful tool to predict the percentage of prosthesis size loss after TAVR. This new index should be taken into consideration in the selection of transcatheter valve sizes to avoid prosthesis under-expansion. Funding Acknowledgement: Type of funding sources: None.